If it's not what You are looking for type in the equation solver your own equation and let us solve it.
y=-8/5(8)+4
We move all terms to the left:
y-(-8/5(8)+4)=0
We get rid of parentheses
y-4+8/58=0
We multiply all the terms by the denominator
y*58+8-4*58=0
We add all the numbers together, and all the variables
y*58-224=0
Wy multiply elements
58y-224=0
We move all terms containing y to the left, all other terms to the right
58y=224
y=224/58
y=3+25/29
| 4x-2(x-5)=-3+x+9 | | (125x700)=150 | | 4(+2)=x+10 | | 2=-8/5x+4 | | 6=-8/5x+4 | | 4n-2n=-11+n | | y=-8/5(3)+4 | | y=-8/5(2)+4 | | 3/4-x=2x | | -11-3y=34 | | x-8/5=x-12/9 | | y=-8/5(-1)+4 | | 42=3(-4a+6 | | 3(7x+8)=2x | | -8n+4n=-4(1+2n)-2(n+1) | | 7x–14=–28 | | -6(x=15) | | 3t+4.41=22.59 | | 233-2u=-21 | | 5/17=x/12 | | 29(m+2)=986 | | 36x20=x | | 5x+9+3x=15 | | 10+5x+4=-2x+x+2 | | u/11-201=-172 | | 4(x)–7=36 | | 5+3.7*d=42 | | 4x–7=36 | | 88=2(c+15) | | |3d|=-6 | | 3x+1+x=-9-4x-10 | | p/5-12=15 |